GAYA BAHASA DALAM PODCAST ANCUR DAN PEMANFAATANNYA SEBAGAI MOTIVASI BELAJAR SISWA - Fitria, Enggar Anisa; Al Ma’ruf, Ali Imron (Universitas Papua, 2025)
In the last decade, podcasts have been widely used by Generation Z with various popular languages. This research aims to examine the podcast